(untitled) (Journal of the College of Languages (JCL), 2017)
Hyperbole is an obvious and intentional exaggeration in the sense that it takes things to such an extreme that the audience goes too far and then pulls itself back to a more reasonable position, i.e. it is an extravagant statement or figure of speech not intended to be taken literally. This paper focuses on the formal and functional perspectives in the analysis of hyperbole which American candidates produce in their speeches in electoral campaigns, for it is hypothesized that candidates in their electoral campaigns use hyperbolic expressions excessively to persuade voters of the objectives of their electoral campaign programs. Hence, it aims to analyze hyperbole in context to determine the range of pragmatic functions that this figure fulfills and to present a formal analysis of hyperbole to demonstrate which formal realizations employed with a hyperbolic function are more or less likely to serve the persuasive aspect of hyperbole. To achieve these aims, three campaign speeches by Barack Obama from the 2012 Presidential Election, chosen at random from the American Presidency Project, were analyzed, and the occurrences of hyperbolic expressions identified. The frequency findings, in terms of the formal analysis, reveal that the exaggerated content found in single words is the type which represents the most common realization of hyperbole in Obama’s speeches. In terms of the functional analysis, the results reveal that emphasis and evaluation appear to be the most prominent functions suggesting that the intended impression on voters is only constructed through the combined effects of these two devices.